Evaluation of disposable microfluidic chip design for automated and fast Immunoassays - Wang, Guochun (Biomicrofluidics, 2017)
We report here, the design and development of a disposable immunoassay chip for protein biomarker detection within ∼1 h. The unique design allows for real-time dynamic calibration of immunoassay for multiple biomarker detections on the chip. The limit of detection achieved for this test chip is 10 pg/ml for IL6, and 50 pg/ml for GFAP with a detection time of 1 h. The prototype instrument used for flowing the reagents through the chip can be easily assembled from off-the-shelf components with the final chemiluminescent detection carried out in a commercial plate reader. Optimization of different aspects of chip design, fabrication, and assay development is discussed in detail.